Improving the management of post-operative acute pain: priorities for change. (2nd November 2015) - Meissner, Winfried; Coluzzi, Flaminia; Fletcher, Dominique; Huygen, Frank; Morlion, Bart; Neugebauer, Edmund; Pérez, Antonio Montes; Pergolizzi, Joseph
Abstract: Poor management of post-operative acute pain can contribute to medical complications including pneumonia, deep vein thrombosis, infection and delayed healing, as well as the development of chronic pain. It is therefore important that all patients undergoing surgery should receive adequate pain management. However, evidence suggests this is not currently the case; between 10% and 50% of patients develop chronic pain after various common operations, and one recent US study recorded >80% of patients experiencing post-operative pain. At the first meeting of the acute chapter of the Change Pain Advisory Board, key priorities for improving post-operative pain management were identified in four different areas. Firstly, patients should be more involved in decisions regarding their own treatment, particularly when fateful alternatives are being considered. For this to be meaningful, relevant information should be provided so they are well informed about the various options available. Good physician/patient communication is also essential. Secondly, better professional education and training of the various members of the multidisciplinary pain management team would enhance their skills and knowledge, and thereby improve patient care. Thirdly, there is scope for optimizing treatment. Examples include the use of synergistic analgesia to target pain at different points along pain pathways, more widespread adoption of patient-controlled analgesia, and the use of minimally invasive rather than open surgery. Fourthly, organizational change could provide similar benefits; introducing acute pain services and increasing their availability towards the 24 hours/day ideal, greater adherence to protocols, increased use of patient-reported outcomes, and greater receptivity to technological advances would all help to enhance performance and increase patient satisfaction. It must be acknowledged that implementing these recommendations would incur a considerable cost that purchasers of healthcare may be unwilling or unable to finance. Nevertheless, change is under way and the political will exists for it to continue.